Incidence, diagnostic, treatment and outcome of patients diagnosed with cancer of the pancreas during 1986–2009: a population-based study - Jonsdottir, Sara B.; Juliusson, Gunnar; Kristinsson, Jon Ö.; Hreinsson, Johann P.; Jonasson, Jon G.; Björnsson, Einar S. (Scandinavian Journal of Gastroenterology, 2018)
To access publisher's full text version of this article click on the hyperlink below OBJECTIVE: Limited data exist on the changes in the epidemiology of pancreatic cancer and outcomes over the last decades in population-based cohorts. We aimed to compare the incidence of pancreatic cancer, diagnostic, treatment and survival among patients diagnosed over the period 1986-2009. MATERIALS AND METHODS: A retrospective, nationwide, population-based study. All patients diagnosed with pancreatic cancer in Iceland in two periods, 1986-1997 (P1) and 1998-2009 (P2) were identified through the Icelandic Cancer Registry and relevant clinical information obtained from medical records. RESULTS: A total of 645 patients were identified, 296 in P1 and 349 in P2 (NS). The incidence during P1 was 6.8 per 100,000 inhabitants and 6.2 during P2 (NS). Among biopsy-proven cancers, adenocarcinoma was diagnosed in 89% of the cases in P1 and in P2 in 93% of the cases. Overall 38 (14%) in P1 underwent resection and 22 (7%) in P2 (p < .0004). Patients diagnosed in P2 had longer survival at 6 months (p = .015, log-rank test) and one year (p = .0206) after diagnosis. A total of 4/296 (1.4%) in P1 survived more than 5 years and 3/349 (0.9%) in P2 (NS). CONCLUSIONS: The incidence among patients with pancreatic cancer in Iceland did not show major changes during the last 20 years. Diagnostic approach has changed considerably demonstrating more patients that are not 'resectable'. Survival rate at 6 months and one year has improved over the last two decades whereas the 5-year prognosis has not improved.